THE CORRELATION OF MUSCLE FIBER AND PERIMYSIUM THICKNESS TO THE QUALITY OF TURKEY BREAST MEAT - Afrida Fatkhiatul Musfiroh; Sabine Janisch; V P Bintoro; Michael Wicke; Yoyok Budi Pramono (Indonesian Food Technologists, 2013)
Turkey meat is one kind of poultry meat which gives contribute for consumer meat demand. Germany as a second exporter of turkey meat has always improving the quality of turkey meat. One of the important attribute which play main role in meat quality is tenderness. The objectives of the research were to measure of muscle fiber and perimysium of two male turkeys in particular amount then makes comparison of the measurement between them. Tracing identifying factors which have strong influence to the tenderness of turkey meat also was done. The data also supported by the values from pH, EC, color, drip loss, grill loss, and shear force. Hybrid XL and Big 6 as two lines of genetically turkeys was used in this study. They lines have different weight in part of carcass where Hybrid XL is bigger than Big 6. Concerning to the diameter of muscle fiber, Hybrid XL has smaller diameter than Big 6. The type of muscle fiber in turkey meat is II B. The analysis of the data was used software Statistic 10.0 ed. The results showed that pH value gives influences to the meat colour. L* would be increasing when pH value was decreasing and meat color turning pale. L* determined by amount of myoglobin inside of meat. The other factors were influenced each other concerning the tenderness of turkey meat. Big 6 breast meat has better tenderness quality and Hybrid XL meat was more profitable because they have heavier part of carcass. Diameter of muscle fiber has strongest factors than others.